Warming and CO2 enhance arctic heterotrophic microbial activity - Vaqué, Dolors; Lara, Elena; Arrieta, Jesús M.; Holding, Johnna; Sa, Elisabet L; Hendriks, Iris E.; Coello-Camba, Alexandra; Alvarez, Marta; Agusti, Susana; Wassmann, Paul; Duarte, Carlos M. (Frontiers in Microbiology, 2019)
Ocean acidification and warming are two main consequences of climate change that can directly affect biological and ecosystem processes in marine habitats. The Arctic Ocean is the region of the world experiencing climate change at the steepest rate compared with other latitudes. Since marine planktonic microorganisms play a key role in the biogeochemical cycles in the ocean it is crucial to simultaneously evaluate the effect of warming and increasing CO2 on marine microbial communities. In 20 L experimental microcosms filled with water from a high-Arctic fjord (Svalbard), we examined changes in phototrophic and heterotrophic microbial abundances and processes [bacterial production (BP) and mortality], and viral activity (lytic and lysogenic) in relation to warming and elevated CO2. The summer microbial plankton community living at 1.4°C in situ temperature, was exposed to increased CO2 concentrations (135–2,318 μatm) in three controlled temperature treatments (1, 6, and 10°C) at the UNIS installations in Longyearbyen (Svalbard), in summer 2010. Results showed that chlorophyll a concentration decreased at increasing temperatures, while BP significantly increased with pCO2 at 6 and 10°C. Lytic viral production was not affected by changes in pCO2 and temperature, while lysogeny increased significantly at increasing levels of pCO2, especially at 10°C (R2 = 0.858, p = 0.02). Moreover, protistan grazing rates showed a positive interaction between pCO2 and temperature. The averaged percentage of bacteria grazed per day was higher (19.56 ± 2.77% d-1) than the averaged percentage of lysed bacteria by virus (7.18 ± 1.50% d-1) for all treatments. Furthermore, the relationship among microbial abundances and processes showed that BP was significantly related to phototrophic pico/nanoflagellate abundance in the 1°C and the 6°C treatments, and BP triggered viral activity, mainly lysogeny at 6 and 10°C, while bacterial mortality rates was significantly related to bacterial abundances at 6°C. Consequently, our experimental ...